Faktor Predisposing, Enabling, dan Reinforcing dengan Keputusan Pembelian Premi BPJS Kesehatan - Rafidah, Fauzia; Adi, Sapto; Ulfah, Nurnaningsih Herya (citeus, 2019)
This study aims to determine the relationship of predisposing, enabling, and reinforcing factors to decision purchase of premium’s BPJS Health in the district Klojen Malang. The research design used was analytic observational with cross sectional approach. The sample was taken using cluster proportionate random sampling technique with 130 respondents who have BPJS Health card’s and domiciled in Klojen district. The results using simultant logistic regression ( X2 = 31,190 > X2table = 22,457) showed that education, knowledge, attitude, acces, income, and officer behaviour have significant relation with purchase decision. The conclusion of this research is predisposing, enabling and reinforcing have relationship with purchase decision of premium’s BPJS Health in Klojen Malang City.